Pressure-jump induced rapid solidification of melt: a method of preparing amorphous materials. (22nd March 2018) - Liu, Xiuru; Jia, Ru; Zhang, Doudou; Yuan, Chaosheng; Shao, Chunguang; Hong, Shiming
Abstract: By using a self-designed pressure-jump apparatus, we investigated the melt solidification behavior in rapid compression process for several kinds of materials, such as elementary sulfur, polymer polyether-ether-ketone (PEEK) and poly-ethylene-terephthalate, alloy La68 Al10 Cu20 Co2 and Nd60 Cu20 Ni10 Al10 . Experimental results clearly show that their melts could be solidified to be amorphous states through the rapid compression process. Bulk amorphous PEEK with 24 mm in diameter and 12 mm in height was prepared, which exceeds the size obtained by melt quenching method. The bulk amorphous sulfur thus obtained exhibited extraordinarily high thermal stability, and an abnormal exothermic transition to liquid sulfur was observed at around 396 K for the first time. Furthermore, it is suggested that the glass transition pressure and critical compression rate exist to form the amorphous phase. This approach of rapid compression is very attractive not only because it is a new technique of make bulk amorphous materials, but also because novel properties are expected in the amorphous materials solidified by the pressure-jump within milliseconds or microseconds.